Acoustic Metamaterials for Noise Reduction: A Review. Issue 6 (29th January 2022) - Gao, Nansha; Zhang, Zhicheng; Deng, Jie; Guo, Xinyu; Cheng, Baozhu; Hou, Hong
Abstract: Noise pollution has become a significant global problem in recent years. Unfortunately, conventional acoustic materials cannot offer substantial improvements in noise reduction. However, acoustic metamaterials are providing new solutions for controlling sound waves, and have huge potential for mitigating noise propagation in particular. Recently, owing to the rapid development of acoustic metamaterials, metamaterials for acoustic noise reduction have drawn the attention of researchers worldwide. These metamaterials are often both light and compact, and are excellent at reducing low‐frequency noise, which is difficult to control with conventional acoustic materials. Recent progress has illustrated that acoustic metamaterials effectively control sound waves, and optimizing their structure can enable functionality based on new physical phenomena. This review introduces the development of acoustic metamaterials, and summarizes the basic classification, underlying physical mechanism, application scenarios, and emerging research trends for both passive and active noise‐reduction metamaterials. Focusing on noise reduction, the shortcomings of current technologies are discussed, and future development trends are predicted. As our knowledge in this area continues to expand, it is expected that acoustic metamaterials will continue to improve and find more practical applications in emerging fields in the future. Abstract : This review introduces the development of acoustic metamaterials, the basic classification, the underlying mechanism, application scenario, and emerging trends for both passive and active noise‐reduction metamaterials. Acoustic metamaterials will continue to improve and the authors would likely believe these unusual metamaterials more practical in this emerging field in future.